2013
DOI: 10.1016/j.bpj.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Skin Membrane Electrical Impedance Properties under the Influence of a Varying Water Gradient

Abstract: The stratum corneum (SC) is an effective permeability barrier. One strategy to increase drug delivery across skin is to increase the hydration. A detailed description of how hydration affects skin permeability requires characterization of both macroscopic and molecular properties and how they respond to hydration. We explore this issue by performing impedance experiments on excised skin membranes in the frequency range 1 Hz to 0.2 MHz under the influence of a varying gradient in water activity (aw). Hydration/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 76 publications
3
80
0
Order By: Relevance
“…The formation of thicker scar tissue and lower new vessel production of control group samples during the first few days of healing may be directly related to the higher electrical resistive response of tissues obtained on the 3rd day of healing. This is also relevant with the decreased water content causing higher electrical resistance due to vasoconstriction and blood clot formation during the inflammation stage of healing [41]. Moreover, due to the existence of wound gap until the 10th day of healing, it is The electrical resistance of skin is also strongly related to the thickness of the newly formed stratum corneum (SC) layer, which dominates the resistive properties of skin in the frequency range of measurements [27,42].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of thicker scar tissue and lower new vessel production of control group samples during the first few days of healing may be directly related to the higher electrical resistive response of tissues obtained on the 3rd day of healing. This is also relevant with the decreased water content causing higher electrical resistance due to vasoconstriction and blood clot formation during the inflammation stage of healing [41]. Moreover, due to the existence of wound gap until the 10th day of healing, it is The electrical resistance of skin is also strongly related to the thickness of the newly formed stratum corneum (SC) layer, which dominates the resistive properties of skin in the frequency range of measurements [27,42].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 A number of studies have suggested additional changes to the layers of the skin occur, particularly in the SC and include altered permeability and flexability, viscoelastic properties, weakened intercellular attachment and changes in electrical impedance properties. [38][39][40][41][42][43][44] The physical structure of the epidermis can be particularly affected. 45,46 However, other studies have suggested that hydration-induced changes to the epidermis are quickly reversed upon removal of the cause.…”
Section: Moist Wound Healingmentioning
confidence: 99%
“…A paper by Börklund et al [26] found that when exposed to a hydrating solution, a w = 0.992, the resistance of the skin is on average 14 times lower with the effective capacitance is 1.5 times higher when compared with dehydrating conditions, a w = 0.826. These changes are largely reversible and have been tested over a 96 hour period.…”
Section: Hydrationmentioning
confidence: 99%
“…where water activity (a w ) is the partial vapour pressure of water in a substance (p) divided by the standard state partial vapour pressure of water (p 0 ) [26]. A paper by Börklund et al [26] found that when exposed to a hydrating solution, a w = 0.992, the resistance of the skin is on average 14 times lower with the effective capacitance is 1.5 times higher when compared with dehydrating conditions, a w = 0.826.…”
Section: Hydrationmentioning
confidence: 99%